Corporate Social Responsibility Initiatives and Community Development: A Review of Literature on the Prospects and Challenges in Developing Countries - Simbai, Mberewere; Kudzanai, Matowanyika; Tinashe, Ruvinga (Indonesian Journal of Community Services, 2024)
Businesses used to exist primarily for the goal of making profits. Corporations, however, are now realizing that they must adopt a socially responsible stance to promote community growth and remain profitable in a fast-changing environment. As a result, there is a growing expectation among stakeholders that businesses should act responsibly towards society in addition to being profit-driven. In this view, corporate citizenship, ethical business practices, and corporate social opportunity are all included in modern corporate social responsibility (CSR). According to the notion, businesses should take society's interests into account by being accountable for how their actions affect their suppliers, consumers, workers, shareholders, communities, and other stakeholders in addition to the environment. This duty demonstrates that companies must act to enhance the welfare of all stakeholders to guarantee the growth and development of communities. This analysis examines the several CSR programs that businesses can implement to support sustainability and community development. By so doing the review considers such possibilities and challenges in implementing CSR initiatives. Academic databases such as Scopus, Google Scholar, Web of Science, and the Directory of Open Access were employed by the researchers for document analysis. The research was hinged on Carrol's theory. The study found that corporates may need to undertake different forms of CSR that include environmental responsibility, ethical responsibility, philanthropic responsibility, and economic responsibility. However, politics and lack of funding have been the major challenges in implementing such initiatives.